2018
DOI: 10.1051/epjap/2018180194
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost deposition of cupric oxide thin films for optoelectronic applications

Abstract: Copper oxide is a compound that has been considered significant owing to its many advantages such as easy availability of copper in huge quantity, its non-toxic nature and the good electrical and optical properties. It is p-type with bandgap range of 1.21-1.51 eV and has potential of absorption of solar spectrum. In this work, sol-gel chemistry is explored to deposit CuO using cupric chloride dihydrate (CuCl 2 · 2H 2 O) with 5, 10 and 15% concentration of EDTA (capping agent) using low-cost dip-coating and ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Gavade et al made a comparison and indicated that the rate constant of Ag-Cu x O-ZnO is higher than that of Au-Cu x O-ZnO [26]. In addition, a p-type CuO semiconductor has received more attention for synthesizing CuO/ZnO heterostructure photocatalysts [27][28][29][30] owing to a narrow direct band gap in the range 1.2-1.5 eV, which favor the formation of p-n junction potential [31]. Noticeably, the emergence of an intrinsic electric field at the interfaces can eliminate the electron-hole recombination since CuO and ZnO have opposite charges.…”
Section: Introductionmentioning
confidence: 99%
“…Gavade et al made a comparison and indicated that the rate constant of Ag-Cu x O-ZnO is higher than that of Au-Cu x O-ZnO [26]. In addition, a p-type CuO semiconductor has received more attention for synthesizing CuO/ZnO heterostructure photocatalysts [27][28][29][30] owing to a narrow direct band gap in the range 1.2-1.5 eV, which favor the formation of p-n junction potential [31]. Noticeably, the emergence of an intrinsic electric field at the interfaces can eliminate the electron-hole recombination since CuO and ZnO have opposite charges.…”
Section: Introductionmentioning
confidence: 99%